Knowledge and attitudes of female genital mutilation among midwives in Eastern Sudan - Ali Abdel Aziem A (BMC, 2012)
Abstract Background Female Genital Mutilation (FGM) or cutting caries legal and bioethical debates and it is practiced in many developing countries. Methods Random selection of 154 midwives was used for the study during June 2012 and through July 2012 aiming to assess knowledge and attitudes of the midwives towards FGM in Eastern Sudan. Results A total of 157 midwives enrolled in this study. They had been practicing for 3 - 44 years (mean SD 19.2 ± 10.3). More than two third of them experienced practicing FGM sometime in their life (127/157, 80.9%). There was low level of awareness of types of FGM practice since only 7% (11/157) identified the four types correctly. 53.5% (84/157) identified type 1 correctly while 18.5% (29/157), 17.8% (28/157) and 15.9% (25/157) identified type 2, 3 and 4 as correct respectively. While 30 (19.1%) of the midwives claimed that all types of FGM are harmful, 76.4% (120/157) were of the opinion that some forms are not harmful and 7 (4.5%) reported that all types of FGM are not harmful. Likewise while 74.5% (117/157) of the interviewed midwives mentioned that the FGM is a legal practice only 25.5% (40/117) were of the opinion that FGM is illegal practice. The vast majority of the respondents (64.3%, 101/157) have an opinion that FGM decreases the sexual pleasure. More than half (53.5%, 84/157) of the participants affirmed that FGM does not increase the risk of HIV transmission. High proportion of the respondents (71.3%, 112/157) did not know whether or not infertility could complicate FGM. Conclusions Thus a substantial effort should be made to discourage the continuation of FGM practice among midwives in Sudan. This might be achieved by improving knowledge and awareness among the midwives and the community